Pediatric acute lymphoblastic leukemia management using multitargeting bioactive natural compounds: A systematic and critical review - Fatemeh Nabizadeh; Saeideh Momtaz; Maryam Ghanbari-Movahed; Farshad Qalekhani; Hadi Mohsenpour; Ina Yosifova Aneva; Anusha Bishayee; Mohammad Hosein Farzaei; Anupam Bishayee (Elsevier, 2022)
Pediatric acute lymphoblastic leukemia (pALL), a malignancy of the lymphoid line of blood cells, accounts for a large percentage of all childhood leukemia cases. Although the 5-year survival rate for children with ALL has greatly improved over years, using chemotherapeutics as its first-line treatment still causes short- and long-term side effects. Furthermore, induction of toxicity and resistance, as well as the high cost, limit their application. Phytochemicals, with remarkable cancer preventive and chemotherapeutic characteristics, may serve as old solutions to new challenges. Bioactive plant secondary metabolites have exhibited promising antileukemic and adjunctive effects by targeting various molecular processes, including autophagy, cell cycle, angiogenesis, and extrinsic/intrinsic apoptotic pathways. Although numerous reports have shown that various plant secondary metabolites can interfere with the progression of malignancies, including leukemia, there was no comprehensive review article on the effect of phytochemicals on pALL. This systematic review aims to provide critical and cohesive analysis of the potential of various naturally-occurring plant secondary metabolites in the management of pALL with the understanding of underlying molecular and cellular mechanisms of action.